Development of EKSIS (ebook ekosistem) to introduce the ecosystem concept in class 3 elementary school - Rucita Ayu Wijaksana; Ani Nur Aeni; Dety Amelia Karlina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to develop and validate the EKSIS product, a learning media based on ecosystem materials designed to introduce the concept of ecosystems to third-grade elementary school students. The research method used is Design and Development (D&D), with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation instrument consists of a five-point Likert scale assessment sheet to measure the quality of the product from two main aspects: product design and content material. The validation results show that EKSIS received an average score of 5 for both assessed aspects, placing it in the